Coffee silver skin as a source of polyphenols: High resolution mass spectrometric profiling of components and antioxidant activity. (January 2016) - Regazzoni, Luca; Saligari, Federica; Marinello, Cristina; Rossoni, Giuseppe; Aldini, Giancarlo; Carini, Marina; Orioli, Marica
Highlights: We analysed the chlorogenic acid profile of some coffee byproducts. Silver skins represent a valuable industrial source of chlorogenic acids. The decaffeination process seems not to alter the silver skins polyphenols content. Abstract: Many beneficial effects of coffee have been ascribed to the presence of chlorogenic acids. For this reason, some green coffee bean decaffeinated extracts claiming several beneficial effects are actually on the market as either nutraceuticals or food supplements. Herein, we compared the polyphenol content of green coffee beans, roasted coffee, spent coffee and silver-skins. The phenolic fraction of all samples was assessed using both colorimetric and HPLC-UV approaches, performing a full detailed identification and quantification of the phenols by liquid chromatography high-resolution mass spectrometry. Furthermore, we also evaluated the antioxidant activity of the different extracts. Notably, silver-skin extract possesses a superimposable profile compared to green coffee beans extract, and such a profile was unaltered by silver-skin decaffeination. This study reveals the perspective of using decaffeinated silver-skins as a low-cost raw material for the preparation of caffeine-free, chlorogenic acid-based food supplements and nutraceuticals.